Gambaran Faktor Risiko Kejadian Penyakit Jantung Koroner di Poliklinik Jantung RSI Siti Rahmah Padang Tahun 2017-2018 - Yushera Atika Sari; Wisda Widiastuti; Betty Fitriyasti (Health and Medical Journal, 2021)
Introduction: CAD occurs indirectly, usually a person will experience a process of narrowing of the coronary arteries in quite a long period of time. Primary survey results that researchers have done at Siti Rahmah Padang Hospital, recorded from 2017-2018 the number of CAD events as many as 115 cases. Aims : To obtain information about an overview of risk factors for the occurrence of coronary artery disease in the heart policlinic of Siti Rahmah Hospital Padang in 2017-2018. Method: This research covers the field of internal medicine and cardiology, this study was conducted at the Islamic hospital Siti Rahmah Padang in May to November 2019. This research used a descriptive method with a cross sectional approach using secondary data from medical records. The affordable population of this study is CAD patients who seek treatment at Siti Rahmah Hospital in Padang in 2017-2018 with 51 samples using Total Sampling technique. Univariate analysis is presented in the form of a frequency distribution table. Results: Based on the results of the study the most age was at the age of 50-59 years, 21 people (41.2%), the most sex was female, 26 people (51%), hypertension, 27 people (52,9%), experienced DM 26 people (51%) were obese, 16 people (31,4%) and hyperlipidemia, 13 people (25,5%). Conclusion : Most age 50-59 years, most sexes of women, most have hypertension, less than half are obese, most have DM and less than half have hyperlipidemia.